Digital Political Marketing and Voter Participation in the 2024 Indonesian Presidential Election: A Bibliometric Literatur Review - Indah Khoirunnissa; Dian Eka Rahmawati (PT. Global Research Collaboration, 2026)
This study maps the development of academic literature on digital political marketing and voter participation in the context of the 2024 Indonesian Presidential Election using a bibliometric approach. Scopus-indexed publications were analyzed with VOSViewer through keyword co-occurrence analysis to identify conceptual relationships, dominant themes, and research clusters. The findings show that “digital political marketing” appears as a central concept connected to communication strategies, target audiences, voter participation, election information, personal branding, and digital media. In addition, “social media” functions as a key node linked to platforms such as Facebook, Instagram, and Twitter/X, as well as to social media campaigns, political communication, and election political participation. These results indicate that the literature mainly discusses digital political marketing through the themes of campaign communication, audience segmentation, candidate image-building, election information dissemination, and voter engagement. This study is limited to Scopus-indexed publications and does not use primary voter data; therefore, the findings represent conceptual patterns in academic literature rather than causal effects of digital marketing on voter behavior. By providing a structured bibliometric mapping of key themes, clusters, and underexplored topics, this research contributes to a clearer understanding of digital political marketing studies and offers directions for future research on digital campaign strategies and voter participation in Indonesia.